Non-apoptotic programmed cell deaths in diabetic pulmonary dysfunction: the new side of advanced glycation end products - Dai, Yimin; Zhou, Shuang; Qiao, Lin; Peng, Zhao; Zhao, Jiuliang; Xu, Dong; Wu, Chanyuan; Li, Mengtao; Zeng, Xiaofeng; Wang, Qian (Frontiers in Endocrinology, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder that affects multiple organs and systems, including the pulmonary system. Pulmonary dysfunction in DM patients has been observed and studied for years, but the underlying mechanisms have not been fully understood. In addition to traditional mechanisms such as production and accumulation of advanced glycosylation end products (AGEs), angiopathy, tissue glycation, oxidative stress and systemic inflammation, recent studies have focused programmed cell deaths (PCDs), especially the non-apoptotic ones, in diabetic pulmonary dysfunction. Nonapoptotic PCDs (NAPCDs) including autophagic cell death, necroptosis, pyroptosis, ferroptosis, and copper-induced cell death have been found to have certain correlations with diabetes and relevant complications. AGEs-AGE receptor (RAGE) axis not only plays an important role in the traditional pathogenesis of diabetes lung disease, but also plays an important role in non-apoptotic cell death. In this review, we summarize novel researches about roles of non-apoptotic PCDs in diabetic pulmonary dysfunction and focused on their interactions with AGEs-RAGE axis.